A influ??ncia do CEO no desempenho da empresa - Tres, Guilherme Smaniotto (2014)
The characteristics of the senior executive team are understood as determining factors for the success of the organization. The companies top executives take the strategic decisions that lead the organization, these decisions affect the company's performance in several dimensions, including the financial results. Thus, using financial indicators provided by the database ECONOM??TICA and information about characteristics of the 73 company??s president, the CEO - Chief Executive Officer, collected through a survey of listed companies Stock Exchange of S??o Paulo, this study proposed to analyze the influence of socio-demographic characteristics of the CEO in the performance of large organizations in Brazil. The results demonstrated that the characteristics of CEO influence differently the performance indicators. The EBITDA is the indicator that was most influenced by the CEO. Apparently, CEOs were more concerned with short-term results, and firms that have CEO with greater diversity of experience and younger get better performance, in more dynamic sectors of the economy companies that have CEO with greater diversity of experience and younger obtain better performance.. This dissertation contributes to companies perceive the CEO as an important figure and which decisively influences the company as a whole, which can serve as a basis for selection and development of top executives and help companies achieve and maintain their competitive advantage.